The Routledge companion to religion and popular culture - Lyden, John; Mazur, Eric Michael (Routledge religion dompanions, 2015)
"Religion and popular culture is a fast-growing field that spans a variety of disciplines. This volume offers the first real survey of the field to date and provides a guide for the work of future scholars. It explores: key issues of definition and of methodology religious encounters with popular culture across media, material culture and space, ranging from videogames and social networks to cooking and kitsch, architecture and national monuments the representation of different religious traditions within the media and popular culture, mainly in the West but also including important non-western spheres such as Bollywood. Students will find the Companion an enjoyable and informative resource, whilst scholars will find it a stimulus to future work in the field"--